Perempuan Sebagai Agen Perubahan Sosial: Membaca Keluaran 1:8-2:10 Dari Perspektif Hermeneutik Postcolonial Feminis - mariance (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
This article aims to read Exodus 1:8-2:10 from a postcolonial feminist perspective by highlighting the role of women in the text who have the ability to act as agents of social change. The injustice and discrimination experienced by women persists for a long time because the influence of patriarchal and kyriarchal culture is still inherent in society. Injustice and discrimination have a negative impact on women, namely physical, economic, psychological losses and the progress of society as a whole. From this, the injustice and discrimination experienced by women needs to be combated. One effort to combat this is by showing the important role of women as agents of social change. This research uses qualitative research methods with a literature study approach. In reading Exodus 1:8-2:10 using postcolonial feminist hermeneutics by bringing the experiences of women in today's life to bring out messages in the biblical text. The women who have a role as agents of social change, namely the Levite woman, the older sister of the baby boy, Sifra, Pua, Pharaoh's daughter and her ladies-in-waiting. There are three things done by women as agents of social change: (1) the fight between two women against what happened; (2) courage as the key to fighting for the right to live; (3) bidders for bright ideas.